Consensus networks with switching topology and time-delays over finite fields. (June 2016) - Li, Xiuxian; Chen, Michael Z.Q.; Su, Housheng; Li, Chanying
Abstract: The consensus problem in networks with both switching topology and time-delays over finite fields is investigated in this paper. The finite field, which is a kind of finite alphabet, is considered due to the fact that networks often possess limited computation, memory, and capabilities of communication. First, by graph-theoretic method, one necessary and sufficient condition is derived for finite-field consensus of switching networks without time-delays. Subsequently, another necessary and sufficient condition on finite-field consensus without time-delays is provided based on FFC property of matrices associated with switching networks. Moreover, by means of the results on delay-free networks, some necessary and sufficient conditions for finite-field consensus of networks with both switching topology and time-delays are obtained. Additionally, it can be shown that switching networks with time-delays present in each self-transmission cannot achieve consensus.